Voicing Code in STEM A Dialogical Imagination - Sengupta, Pratim (The MIT Press, 2021)
An exploration of coding that investigates the interplay between computational abstractions and the fundamentally interpretive nature of human experience. The importance of coding in K-12 classrooms has been taken up by both scholars and educators. Voicing Code in STEM offers a new way to think about coding in the classroom-one that goes beyond device-level engagement to consider the interplay between computational abstractions and the fundamentally interpretive nature of human experience. Building on Mikhail Bakhtin's notions of heterogeneity and heteroglossia, the authors explain how STEM coding can be understood as voicing computational utterances, rather than a technocentric framing of building computational artifacts. Empirical chapters illustrate this theoretical stance by investigating different framings of coding as voicing. Understanding the experiential nature of coding allows us to design better tools and curricula for students, and enables us to see computing as experience beyond the mastery of symbolic power. Arguing for a critical phenomenology of coding, the authors explain that the phenomenological dimension refocuses attention on the fundamentally complex nature of human experiences that are involved in coding and learning to code. The critical dimension involves learning to recognize voices that historically have received less attention.